Light and oxygen induced degradation limits the operational stability of methylammonium lead triiodide perovskite solar cells. Issue 5 (13th April 2016) - Bryant, Daniel; Aristidou, Nicholas; Pont, Sebastian; Sanchez-Molina, Irene; Chotchunangatchaval, Thana; Wheeler, Scot; Durrant, James R.; Haque, Saif A.
Abstract : Here, we demonstrate that light and oxygen-induced degradation is the main reason for the low operational stability of methylammonium lead triiodide (MeNH3 PbI3 ) perovskite solar cells exposed to ambient conditions. Abstract : Here, we demonstrate that light and oxygen-induced degradation is the main reason for the low operational stability of methylammonium lead triiodide (MeNH3 PbI3 ) perovskite solar cells exposed to ambient conditions. When exposed to both light and dry air, unencapsulated MeNH3 PbI3 solar cells rapidly degrade on timescales of minutes to a few hours. This rapid degradation is also observed under electrically bias driven current flow in the dark in the presence of O2 . In contrast, significantly slower degradation is observed when the MeNH3 PbI3 devices are exposed to moisture alone ( e.g. 85% relative humidity in N2 ). We show that this light and oxygen induced degradation can be slowed down by the use of interlayers that are able to remove electrons from the perovskite film before they can react with oxygen to form O2 − . These observations demonstrate that the operational stability of electronic and optoelectronic devices that exploit the electron transporting properties of MeNH3 PbI3 will be critically dependent upon the use of suitable barrier layers and device configurations to mitigate the oxygen sensitivity of this remarkable material.